Effect of Current, Voltage, Temperature, and Time Variations on Thickness of Steel using Electroplating Process - Budiana, Budiana; Situmorang, Choklin Brema; Maulidiah, Hana Mutialif; Puspita, Widya Rika (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
The use of low carbon steel is categorized as one of the supporting materials in industrial and technological developments because it has high ductility and toughness. However, low carbon steel has limitations in terms of corrosion resistance. There are several ways to increase corrosion resistance in steel. One of them is by providing a layer of protection on the steel surface. The steel plating method used is the electrolysis method or electroplating method. This study aims to determine the influence of variations in current, voltage, temperature, and time on the thickness of the coating formed on steel. The steel plating process is carried out by electroplating process where the coating material or anode is Nickel (Ni) with dimensions (60 mm x 30 mm x 0,1 mm). In comparison, the coated object or cathode is SK5 steel with dimensions (50 mm x 20 mm x 0,3 mm). The aim of this study is to investigate the effect of Current, Voltage, Temperature, and Time Variations on the thickness of steel using electroplating processes. Moreover, all factors will be optimised to achieve the best thickness for steel. Consequently, the corrosion resistance of SK5 can be significantly improved by increasing its thickness. The current variations were used 1A, 2A, 3A, and 4A; voltage variations were used 3V, 6V, 9V, and 12V; temperature variations were used 30°C, 40°C, and 50°C; and times variations were used 0 m, 5 m, 10 m, and 20 m. Based on the results of research that has been carried out on all samples, it is concluded that current, voltage, temperature and time affect the thickness of the sample in the electroplating process. The current, voltage, temperature and time values are linearly related to the thickness resulting from the electroplating process.